Pengetahuan Tentang Manfaat Pohon Pinus Pada Masyarakat di Desa Matarawa, Kecamatan Watopute Kabupaten Muna - Rahmi, Rahmi; Sifatu, Wa Ode; Hartini, Hartini (JURNAL KABANTI: Kerabat Antropologi, 2025)
This study aims to explore the local knowledge of the benefits of pine trees among the community in Matarawa Village, Watopute District, West Muna Regency. The research seeks to answer the question: (1) What is the community's knowledge regarding the benefits of pine trees? This study uses Ahimsa-Putra's Ethnoscience Theory. The research method applied is qualitative with purposive sampling, and data were analyzed using observation, interviews, and documentation. The data analysis is descriptive qualitative, which involves describing the research findings based on field data, followed by interpretation and conclusion. The results show that the community possesses local knowledge about the benefits of pine trees as a cultivated commodity. This includes understanding the uses of pine trees and how to care for them, as reflected in the following categories: Lahano Puguhuno Pinusu (Pine Tree Land), Defepili Wine (Seed Selection), Hasilino Kebhae Folono (Resin Harvest), and Laano Sau Pinusu (Pine Tree Trunk).